PENGARUH KOMUNIKASI ORGANISASI, MOTIVASI KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MR. DIY KOTA BEKASI - Haratua, Chandra S.; Putri, Indriani Jelita; Indriyani, Novi; Berlian, Kartika Sari; Nur'aini, Nur'aini (INTELEKTIUM, 2024)
The purpose of variable is studied by the author to find out how employee performance MR. DIY Bekasi City is influenced by organizational culture, work motivation, and organizational communication. This study uses a combination of survey methodology and correlational approach. The research sample of 100 employees was selected randomly. Information was obtained from questionnaire data. The results of the multiple regression analysis were carried out using SPSS. Classical assumption tests, such as multicollinearity and normality tests, were used in the data analysis procedure. such as normality and multicollinearity tests, were used in the data analysis procedure. The statistical tests are multiple regression, correlation coefficient test, and hypothesis. The results of the hypothesis test indicate a fairly large relationship between the dependent variable and the independent variable.